PENYESUAIAN DIRI ANAK DALAM KELUARGA PASCA PERCERAIAN DI NAGARI AMPANG KURANJI KEC KOTO BARU KAB DHARMASRAYA - Evani, Mutia - (Pendidikan Sosiologi, 2014)
This research is motived by the divorce done by parents to and the relationship so resulted in the childâs mental. Children of divorce experience mild depression and also affects the way children interact with the surrounding environment. Changes that ocuur in children, it requires children to be able to control and direct the actions, attitudes or behaviors to achieve goals that are able to provide a commitment to be yourself and be accepted by the environment. This study aimed to describe the adjusment of children in the family after his parent divorced. Theory used is structural functionalism proposed Talcott Parsons. This study used a qualitative approach and descritive. Informants in this study werw : 1) children (aged under 14 years), 2) children who come from divorced parents, and 3) his parents divorced a maximum 2 years and unmarried. The selections of informants in this study using Purposive Sampling technique. The type of data used is primary data and secondary data. Method of data collections was done in three ways : 1) interviews, 2) observation (non-participant observation), 3) study documentation. The unit of analysis is the individual that children from divorced families. Analysis of the data used by the mode of interactive data analysis (Miles and Huberman) this includes four stages : 1) the stage og data collection, 2) data reduction phase, 3) the stage of presentation of data, 4) the stage of cobclusion. The results of this study are forms of adjustment that is done by children : 1) quit school to reduce household expenses, 2) following extracurricular school, 3) help parents, 4) go to surau, and 5) follow the activities outside.